An open‐label positron emission tomography study to evaluate serotonin transporter occupancy following escalating dosing regimens of (R)‐(–)‐O‐desmethylvenlafaxine and racemic O‐desmethylvenlafaxine. Issue 3 (13th December 2017) - Frankle, W. Gordon; Robertson, Brigitte; Maier, Gary; Paris, Jennifer; Asmonga, Deanna; May, Maureen; Himes, Michael L.; Mason, N. Scott; Mathis, Chester A.; Narendran, Rajesh
Abstract: SEP‐227162 [ R (–)‐ O ‐desmethylvenlafaxine] is an enantiomer of the venlafaxine metabolite O ‐desmethylvenlafaxine (ODV, Pristiq™, Wyeth). This study compared the serotonin transporter (SERT) occupancy achieved by SEP‐227162 and ODV, at daily doses of 25, 50, 100, and 150 mg using [ 11 C]DASB positron emission tomography (PET). Sixteen healthy male subjects participated in one of four dose groups ( N = 4 per group) during which they were administered two doses of the study drug (SEP‐227162 or ODV). For each study drug, total daily doses of 25, 50, 100, and150 mg were studied. Subjects underwent three PET scans with [ 11 C]DASB. A baseline, off‐medication, scan was performed prior to dosing and a [ 11 C]DASB PET scan was performed after 72 hr at each dose level. [ 11 C]DASB binding potential (BPND ) was calculated using the simplified reference tissue method. SERT occupancy was calculated as the change in BPND (ΔBPND ) from baseline scan to the on‐medication scan relative to the baseline BPND value. SEP‐227162 and ODV significantly reduced regional distribution volumes and region BPND values in a dose‐dependent manner. Across all doses ODV produced significantly greater SERT occupancy than SEP‐227162 (ANOVA F = 21.8, df = 1, 23, p < .001). The total daily dose required to provide 50% SERT occupancy was 24.8 mg for SEP‐227162 and 14.4 mg for ODV. In vitro data suggests a ratio of 3.3:1 for binding at human SERT for SEP‐227162 relative to ODV. Our study suggests a ratio of 1.7:1, highlighting the value of in vivo imaging in the drug development process. Abstract : It has been shown that minimally effective doses of SSRIs (including paroxetine, sertraline, citalopram, fluoxetine, venlafaxine) responsible for antidepressant activity clinically correspond to steady‐state serotonin transporter (SERT) occupancies of ∼80%. This study examined the SERT occupancy of SEP‐227162, an enantiomer of desvenlafaxine (Pristiq TM, Wyeth), as well as the racemic compound, desvenlafaxine. SEP‐227162 did achieve >80% occupancy, but at doses which were ∼2× those of the racemic compound highlighting the value of in vivo imaging in the drug development process for initial dosing decisions.